Quantifying Patient-Specific in vivo Coronary Plaque Material Properties for Accurate Stress/Strain Calculations: An IVUS-Based Multi-Patient Study - Wang, Liang; Zhu, Jian; Maehara, Akiko; Lv, Rui; Qu, Yangyang; Zhang, Xiaoguo; Guo, Xiaoya; Billiar, Kristen L.; Chen, Lijuan; Ma, Genshan; Mintz, Gary S.; Tang, Dalin (Frontiers in Physiology, 2021)
Introduction: Mechanical forces are closely associated with plaque progression and rupture. Precise quantifications of biomechanical conditions using in vivo image based computational models depend heavily on accurate estimation of patient-specific plaque mechanical properties. Currently, mechanical experiments are commonly performed on ex vivo cardiovascular tissues to obtain the plaque material properties. Patient-specific in vivo coronary material properties are scarce in the existing literature. Methods: In vivo Cine intravascular ultrasound (IVUS) and virtual histology IVUS slices were acquired at 20 plaque sites from 13 patients. Three-dimensional thin-slice structure-only model was constructed for each slice to obtain patient-specific in vivo material parameters values following an iterative scheme. Effective Young’s modulus (YM) was calculated to indicate the plaque stiffness for easy comparison purpose. IVUS-based 3D thin-slice models using in vivo and ex vivo material properties were constructed to investigate their impact on plaque wall stress/strain (PWS/PWSn) calculations. Results: The average YM values in axial and circumferential directions for the 20 plaque slices were 599.5 kPa and 1042.8 kPa, respectively, 36.1% lower than those from published ex vivo data. The YM values in circumferential direction of the softest and stiffest plaques were 103.4 kPa and 2317.3 kPa, respectively. The relative difference of mean PWSn on lumen using in vivo and ex vivo material could be as large as 431%, while the relative difference of mean PWS was much smaller, about 3.07% on average. Conclusion: There is a large inter-patient and intra-patient variability in in vivo plaque material properties. In vivo material has great impact on plaque stress/strain calculations. In vivo plaque material properties have greater impact on strain calculations. Large-scale patient studies are needed to further verify our findings.